Breast cancer in the oldest old (≥ 89 years): Tumor characteristics, treatment choices, clinical outcomes and literature review. Issue 4 (April 2021) - Di Lascio, Simona; Tognazzo, Enrico; Bigiotti, Sara; Bonollo, Marta; Costa, Alberto; Pagani, Olivia; Meani, Francesco
Abstract: Introduction: Risk of breast cancer increases with age and very few data are available in patients older than 89. Methods: A retrospective analysis on patients aged 89 and older treated between 2008 and 2019 at our certified breast center. The aim was to analyze clinical characteristics, decision-making, treatment, outcomes and open questions regarding this subpopulation for which there is a lack of guidelines. Results: 58 patients included. Tumor characteristics were analyzed, 85% patients underwent surgery of which 44% had a mastectomy. The median follow-up and overall survival were 20 and 76 months, respectively.The median survival of metastatic and non-metastatic patients were 14 and 50 months, respectively. Most patients did not receive any adjuvant treatment and among these 14% had a relapse. Conclusions: Elderly patients should not be under or over-treated because of their age; they represent a large heterogeneous group deserving a sub-stratification for a better tailored treatment.